Long-Term Market Outlook (Norges Bank, 2006)
This Market Report will establish a set of investment beliefs for the 15 year horizon we shall be using in the ensuing Portfolio Reports, for the "Government Pension Fund - Global" and the "Foreign Reserves", respectively. The first chapter presents three alternative scenarios for the world economy. The scenario that we consider to be most likely will be the basis of most of our market analysis. The two other scenarios are less likely, but include some of the major downside risks to the market returns. These scenarios will be used for stress-testing our recommendations of asset allocation in the ensuing Portfolio Reports. The developments described in the scenarios will represent the macroeconomic environment, or state of the world, on which the expected returns and volatilities in the global capital markets are conditioned. The different asset classes and their co-variation will be discussed separately in chapters 2-7. Chapter 2 briefly considers the foreign exchange markets, where our long term assumption will be one of no expected changes. But we will discuss some major risk factors. Chapter 3 establishes the covariance matrix that we shall be using in the Portfolio Reports. We use both yearly and monthly data to extract reasonable estimates for our 15 year horizon. We find only a modest horizon effect on the estimates. Chapters 4 and 5 discuss the expected returns in fixed income and equity, which are the two asset classes where the Pension Fund and the Foreign Reserves are currently invested. Our underlying assumption is that the pricing in these markets will tend to revert to a long term mean level. In these chapters we pay special attention to the small cap equity segment and to the high yield fixed income segment, to assess whether these two segments should be included in the benchmark portfolio. Chapters 6 and 7 discuss private equity, real estate and infrastructure, which are asset classes where neither the Pension Fund nor the Reserves are currently not invested. The purpose is to establish expected returns and co-variation patterns that will later be used to assess the benefits of including any of these asset classes in the portfolio. Again, the assumption is that the pricing will have some mean reversion properties. The investment beliefs discussed is this Report will be the basis for our recommendations on asset allocation. That part of the analysis will be presented in separate Portfolio Reports for the Pension Fund and the Foreign Reserves.
hdl:11250/2508016
Keywords: 330